2019
DOI: 10.3390/molecules24081529
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Derivatives of Benzofuran as Potential Anticancer Agents

Abstract: The results of our previous research indicated that some derivatives of benzofurans, particularly halogeno-derivatives, are selectively toxic towards human leukemia cells. Continuing our work with this group of compounds we here report new data on the synthesis as well as regarding the physico-chemical and biological characterization of fourteen new derivatives of benzofurans, including six brominated compounds. The structures of all new compounds were established by spectroscopic methods (1H- and, 13C-NMR, ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The interest in heterocyclic compounds due to their special medicinal properties. The FTIR studies, 1 H NMR and elemental analysis indicated the formation of benzoforan and its derivatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interest in heterocyclic compounds due to their special medicinal properties. The FTIR studies, 1 H NMR and elemental analysis indicated the formation of benzoforan and its derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…Benzofuran derivatives are a major group of biologically active heterocycles which are usually important constituents of plant extracts used in medicinal chemistry for their various biological activities. [1][2][3] Due to their diverse activities, much attention has been paid to synthetic strategies to access these systems, and a number of methods have been developed. 4 Pyrolysis of 2-pyrone at 900-1000 o C in a stream of nitrogen leads to ring contraction into furan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, benzofuran and its derivative also have antitumor activity against MCF-7 dan PC-3. [15][16][17][18][19] Other compounds that are detected in the methanol extract of G. versteegii Buaya are α-Caryophyllene (6) β-Santalol (7). α-Caryophyllene (6), known as humulene is sesquiterpenes that is found in the essential oil.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…In recent years, natural- and synthetic furan-based ( Figure 1 ) based chemotherapeutic agents have attracted the attention of medicinal chemists to develop novel pharmacological agents with diverse pharmacophores andhave expanded the scope and treatment of various diseases [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%